Importance of Supply Chain Flexibility Dimensions Rated by Industry - Jeeva, Ananda; Guo, H. (HumanPub by AAHSRC, 2012)
This paper explores how the industry rates each of the five supply chain flexibility dimensions in supply chain management and operations based on the feedback from more than 200 manufacturing companies in Australia. Statistical classifications are used to identify patterns of consensus on these factors affecting the business operations of supply chain management in the surveyed companies. Our study shows that different sized companies rated these factors differently although some common patterns existed among many manufacturers. This knowledge is important in business decision making in different circumstances.